Indicadores de qualidade do leite bovino orgânico em duas propriedades leiteiras certificadas do Estado de São Paulo - Siqueira, A.k [UNESP] (2012)
This study evaluated the chemical composition, total bacterial count, the level of cellularity and presence of antimicrobial residues in milk from two small farms in organic production system in the state of São Paulo, Brazil, based in NI 062-MAPA. The milk of the Property I had the mean of CCS 7.13 x 10(5) cells/mL and the Property II had 3.27 x 10(5) cells/mL. The averages of CBT were, respectively, 7.80 x 10(5) cells/mL in the Property I and 6.15 x 10(5) cells/mL in Property II. The Property I presented as an average of 3.10% of fat, 3.26% of protein and 4.54% of lactose, while the Property II presented 3.44% of fat, 3.39% of protein and 4.50% of lactose in 12 months assessed. The presence of residues of antimicrobial drugs was detected in six samples (6.97%) of the Property I and 16 (9.24%) of Property II. The results obtained reveal failure in the percepts of organic production.